Survey of Philippine research on the economics of agriculture - Balisacan, Arsenio M. (1989)
The first of a three-part survey on the economics of Philippine agriculture, this paper focuses on empirical studies regarding the determinants of fertilizer use, and the role of input and output subsidies in agricultural development. Based on a simple conceptual framework for the analysis of resource use efficiency in agriculture, it interprets the results of empirical studies on fertilizer use in the Philippines. It also assesses the justifications typically advanced for input subsidies. Finally, lessons for policy and future research as gleaned from the survey of materials are pointed out.
Keywords: Agricultural economics; Fertilizers -- Utilization; Agricultural research